PEMBERDAYAAN MASYARAKAT MELALUI PEMBUATAN AQUAPONIK RAMAH LINGKUNGAN SEBAGAI SOLUSI PERTANIAN BERKELANJUTAN DI AISYIYAH CABANG MEDAN PERJUANGAN - Salsabila; Aflahun Fadhly Siregar; Rini Susanti; Riris Nadia Gurning (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2025)
Aquaponics is an environmentally friendly agricultural alternative that integrates fish farming and plant cultivation within a single ecosystem. This concept is particularly suitable for household-scale application, as it enhances the use of home yards and supports family food security. This Muhammadiyah Community Partnership Program aimed to: (1) improve the knowledge and skills of members of Aisyiyah Branch Medan Perjuangan in constructing aquaponic systems, and (2) raise awareness of the importance of environmentally based sustainable agriculture. The training was conducted using a participatory approach involving socialization, hands-on practice, and active discussion. The program successfully increased participants' awareness and motivation to utilize their home yards productively. Participants demonstrated high enthusiasm throughout the activity, with hopes that similar training initiatives could be extended and developed in other communities.